Effect of Fertilizer Levels and Row Spacings on Growth and Yield of Foxtail Millet (Setaria italica L.) - Jhansi, K.; Karanjikar, P. N.; Suryavanshi, V. P.; Sneha, S. B.; Lokhande, S. S. (International Journal of Economic Plants, 2025)
The field experiment was conducted during kharif, 2023 at Experimental Farm, Department of Agronomy, College of Agriculture, Latur, to study effect of fertilizer levels and row spacings on growth and yield. The experiment was laid out in Factorial Randomized Block Design with two factors and replicated thrice. First factorconsisted of three fertilizer levels viz., fertilizer level-1:75% , fertilizer level-2: 100% and fertilizer level-3: 125% recommended dose of fertilizer, second factor consisted of three-row spacing viz., 2 row spacing-1: 22.5 ×10 cm2, row spacing- 2: 30×10 cm2 and row spacing-3: 45×10 cm2. The results revealed that application of 125 % RDF recorded significantly higher plant height (132.27 cm), number of tillers plant-1 (4.09), number of functional leaves plant-1 (23.84), leaf area plant-1 (2.76 dm2), dry matter plant-1 (20.91 g), LAI (3.50), grain (2833 kg ha-1), straw (8398 kg ha-1) and biological yield (11232 kg ha-1). Among row spacings 22.5×10 cm2 recorded significantly higher plant height (128.95 cm), number of functional leaves plant-1 (23.58), leaf area plant-1 (2.66 dm2), Leaf area index (3.45), grain (2829 kg ha-1), straw (8300 kg ha-1) biological yield (11130 kg ha-1) and harvest index (25%) which was comparable with 30×10 cm2 and significantly superior over 45×10 cm2. Number of tillers plant-1 (3.90) and dry matter plant-1 (20.44 g) were significantly higher with 45×10 cm2 row spacings, which was comparable with 30×10 cm2 and significantly superior over 22.5×10 cm2.